Early Recognition of Anomalous Origin of Right Pulmonary Artery From The Ascending Aorta with Minimal Limited Resources - Sukmapermata, Bunga; Yanti, Ni Putu Veny Kartika; Gunawijaya, Eka (CV. Publikasi Indonesia, 2025)
The anomalous origin of the right pulmonary artery (AORPA) is a rare congenital heart defect with a poor prognosis if not surgically corrected. Atypical symptoms often lead to underdiagnosis and delayed treatment, necessitating timely and accurate examination. The utility of diagnostic tools, especially in resource-limited settings, remains a subject of debate. This research aims to assess the effectiveness of echocardiography and cardiac CT in detecting AORPA in children suspected of having congenital heart disease (CHD), compared to catheter angiography and/or surgery. A case report of a male term newborn presenting with respiratory distress and heart failure was presented. Initial diagnosis was made via echocardiography, which was later confirmed by computed tomography angiography (CTA). A literature search was conducted using PubMed, Google Scholar, and ScienceDirect with keywords such as